20 YEARS OF ARABIC LEARNING IN THE SCIENTIFIC TRADITION OF UIN ALAUDDIN MAKASSAR: ANTHROPOLINGUISTIC PERSPECTIVE FROM 2001 TO 2021 (International Conference on Social and Islamic Studies, 2021)
Arabic learning activities in the scientific tradition of UIN Alauddin Makassar in the last 20 years, in this case from 2001 to 2021, have gone through a long historical process. During this time, several innovative Arabic learning programs have been developed, in this case the Foreign Language Intensification Program (PIBA), the Enlightenment of Faith and Life Skills Program (PIKIH), the Character Building Program (CBP), and are currently returning to the Intensification of Foreign Languages (PIBA) with an orientation towards strengthening the Testof Arabic as a Foreign Language (TOAFL). In the anthropolinguistic perspective which includes, 1) language aspect in the form of learning Arabic which includes the study of paralinguistic, proxemic or kinetic texts and co-texts, 2) culture aspect in the form of scientific traditions which include studies of cultural contexts or co-texts of material elements and 3) other aspects of human life in the study of constructive relations between Arabic learning and scientific traditions that cover social contexts, situations, and ideologies, it can be seen that Arabic language learning in the scientific tradition of UIN Alauddin Makassar always moves dynamically in the locus of scientific philosophy which is the magnum opus of policy-making programs of innovative Arabic learning in support of the institutional vision.